Hi, I'm having trouble with the second part of this question and could really use a nudge in the right direction...
Let a, b and c be three vectors such that a+b+c=0. Show that a x b = b x c = c x a and explain what this means geometrically.
I've proved that a x b = b x c = c x a by means of expanding the two parts of the equation and substituting values in etc, but I'm stuck on the second bit. I know that a+b+c =0 means that a, b and c form a triangle... but beyond that I'm not sure what else to say. How do I relate this back to a x b = b x c = c x a?
Your help would be greatly appreciated. Cheers!